MEMBANGUN PARIWISATA KOLABORATIF: PERAN AKTOR PENTAHELIX DI NAGARI GANGGO MUDIAK - Bella Yulia Anugrah; Erwin Erwin; Syahrizal Syahrizal (Kepariwisataan: Jurnal Ilmiah, 2025)
The development of tourism based on the Pentahelix model requires effective collaboration among five key actors: government, academics, business, community, and media. This study explores how these actors contribute to the tourism development of Nagari Ganggo Mudiak, a village in West Sumatra known for its historical and geographical significance, particularly the Equator Monument area. Using a qualitative approach with a case study method, data were collected through observation, in-depth interviews, and documentation. The findings show that while the government plays a dominant role in infrastructure development, the involvement of other actors remains limited and fragmented. Academics are present through research but lack implementation roles. Local businesses operate independently without structured partnerships, and community participation has declined due to the absence of inclusive decision-making mechanisms. The media's role is also sporadic and uncoordinated. This study concludes that the Pentahelix collaboration in Ganggo Mudiak is still symbolic rather than integrative. Strengthening coordination, participatory mechanisms, and contextualizing development within local cultural values are crucial for achieving sustainable and inclusive tourism.